Antipyretic and Antinociceptive Properties of the Aqueous Extract and Saponin from an Edible Vegetable- Vernonia Amygdalina Leaf - PC, Adiukwu; FIB, Kayanja; GK, Nambatya; S, Rugera; JOC, Ezeonwumelu; JK, Tanayen; BJ, Murokore; O, Twikirize; S, Twinomujuni; D, Byamugisha; Imanirampa, L (African Journal of food, agriculture, nutrition and development, 2013)
Vernonia amygdalina is commonly used for food and health purposes. The processing of the leaf for food is usually aimed at removing bitter tasting principles like saponins. This study was designed to determine the antipyretic and antinociceptive properties of the aqueous extract, crude saponin and the chromatographic fraction of the crude saponin from the leaf. In the antipyretic evaluation, anal temperature change in fasted rats with prior induced pyrexia using intra-peritoneal administered 15% w/v Saccharomyces cerevisiae, was measured four hours after dose administration. In the antinociceptive evaluation, 0.6% acetic acid solution administered by intra peritoneal route at a dose of 15 ml/kg was used to induce writhing in the writhing test; hot plate at 55 °C ± 1 to induce thermal pain in the hot plate test; and cold mixture of water and ethylene glycol (1:1) maintained at -10 °C to initiate pain sensation in the cold tail flick tests. Antipyretic data showed significant (P ≤ 0.05) anal temperature decrease for all the test doses compared to the placebo. This was markedly observed with the aqueous extract at 0.55 oC ± 0.03 anal temperature decrease, compared to the 0.29 0C ± 0.01 of the crude saponin, at a similar dose level of 400 mg/kg. At 200 mg/kg dose, the crude saponin induced an anal temperature decrease of 0.14 0C ± 0.02. This was higher than the response obtained with the chromatographic fraction which produced 0.06 0C ± 0.01 anal temperature decrease. Antinociceptive data was significant (P ≤ 0.05) for the crude saponin in the writhing (52.58 % antinociceptic effect) and hot plate tests (14.24 maximum percent analgesia), contrary to observation in the cold tail flick test. Findings showed the antipyretic and non-steroid like antinociceptive property of the crude saponin, which may support the rationale for the use of Vernonia amygdalina leaf to reduce fever and/or pain.
Keywords: Anal temperature; Writhing; Pain; Pyrexia